Comparación de los cambios estructurales en la superficie dental coronal y radicular, al utilizar instrumentos manuales y ultrasónicos en dientes uniradiculares, estudio in vitro - Velandia Daza, Sergio; Sánchez Claros, Diana Ximena (Universidad Antonio Nariño, 2023)
Periodontal therapy is the elimination of bacterial plaque on the tooth and root surface. It is performed by scaling and root planing, which provides us with a biologically acceptable root surface for the health of the periodontal tissues. Objective: Describe the structural changes caused by the coronal and root tooth surface using ultrasonic and manual instruments using electron microscopy.